Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2008
DOI: 10.1145/1357054.1357084
|View full text |Cite
|
Sign up to set email alerts
|

Measuring trust in wi-fi hotspots

Abstract: Pervasive systems provide services that are situated within specific contexts. An everyday example of this is Wi-Fi hotspots. Factors such as branding and presentation are known to affect whether users are prepared to invest trust in services, but little is known about trust in situated services. This paper describes an experiment to measure de facto trust in Wi-Fi hotspots in public places, as opposed to examining trust behaviour in a simulated lab setting. We investigated two hypotheses about the effect of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…From this data we can draw the conclusion that sporting facilities work well as settings for interactive displays. This may be due to several factors, such as a high number of children and teenagers, but also the extent to which the physical environment instills trust in users, as shown in [17]. From our empirical evidence we have found that youngsters often have an open view on new technology, and are willing to try it out without encouragement or external reward.…”
Section: Towards Understanding Users' In-situ Behaviourmentioning
confidence: 71%
“…From this data we can draw the conclusion that sporting facilities work well as settings for interactive displays. This may be due to several factors, such as a high number of children and teenagers, but also the extent to which the physical environment instills trust in users, as shown in [17]. From our empirical evidence we have found that youngsters often have an open view on new technology, and are willing to try it out without encouragement or external reward.…”
Section: Towards Understanding Users' In-situ Behaviourmentioning
confidence: 71%
“…An alternative method is to observe the activity and interactions of unidentified mobile users in public spaces (e.g., a train, an airport, a town square, etc. [12]), although crossinterpreting the findings with those from, for instance, interviews with identified participants would be difficult.…”
Section: The Challenges With Studying Mobile Privacymentioning
confidence: 99%
“…This complexity places great strain on communication systems with issues in the management of the interactions and the ability to enable the delivery of services whilst maintaining security [29]. Service delivery demands knowledge (contextual information) which identifies user(s) environmental and proximate states, and network infrastructure to effectively target service provision.…”
Section: B Large Scale Distributed Systemsmentioning
confidence: 99%
“…It has been observed in [30] that client server architectures are characterized by the dependence on a central server; LSDS are characterized by the client server paradigm where services provided in distributed systems, often implemented using cloud-based solutions [1,2], are becoming pervasive and ubiquitous [2,29]. In interactions in using ad hoc networks the dynamic nature of such networks presents issues in connecting to a globally accessible server.…”
Section: B Large Scale Distributed Systemsmentioning
confidence: 99%